A Bibliometric Analysis of Nanocrystalline Cellulose Research as Medical Implant Using VOSviewer - Deaniar Hafilah; Asep Bayu Dani Nandiyanto (JURNAL KEDOKTERAN DIPONEGORO (DIPONEGORO MEDICAL JOURNAL), 2022)
Background: Nanocrystalline cellulose has potential for biomedical applications due to its abundant material availability, biodegradability, biocompatibility, and low weight. Research on nanocrystalline cellulose as medical implants has rarely been studied in the past 10 years, although this material has tremendous potential such as bone implants and cardiovascular implants. Objective: This study aims to analyze the development of research on nanocrystalline cellulose as medical implants using a bibliometric approach with computational analysis using VOSviewer. Methods: The article data was obtained using the Publish or Perish software by retrieving the database from Google Scholar. The keyword “nanocrystalline cellulose, medical implants, biomedical" is used with the publication time span from 2012 to 2020. Data processing uses Microsoft Excel. Computational mapping using VOSviewer. Results: Research on the application of nanocrystalline cellulose has been carried out several times, this can be proven from computational mapping analysis using VOSviewer which shows the term "nanocrystalline cellulose" is in the same cluster as the term "medical implant". However, research on the application of nanocrystalline cellulose as medical implants is still rarely carried out, this is evidenced by the small frequency indicated by the two terms. Conclusion: Based on the results of mapping the collected article data, research on the application of nanocrystalline cellulose as medical implants is an interesting topic. However, this topic is still rarely studied. Therefore, this review can be a starting point for selecting the topic of research on the application of nanocrystalline cellulose materials as medical implants as a consideration for determining the research theme to be taken.